EFFECTS OF USING HYDROXIAPATITE-GELATIN GEL AND ROSELLA EXTRACT TO PREVENT RELAPSE IN ORTHODONTIC TREATMENT - Auliadini, Sabrina Fitri; Pakpahan, Evie Lamtiur (Universitas prof. Dr. Moestopo (Beragama), 2024)
To correct malocclusion and malposition in dentistry using orthodontic treatment. Teeth that have moved through the bone with orthodontic devices tend to return to their original position or what is usually called relapse. Relapse is when the teeth return to their original position before orthodontic treatment was carried out. Relapse prevention can be achieved using mechanical devices but there are still some limitations. The use of scaffolds can be a solution in preventing tooth relapse because scaffolds can support cells to grow and develop into new bone in the damaged area. The scaffold components are hydroxyapatite, gelatin, and rosella flower extract which contains flavonoids to inhibit bone resorption. To find out whether these components are toxic or not before they are applied to the human body, a cytotoxicity test is carried out, which is a laboratory study. This research was carried out by incubating the hydroxyapatite scaffold, gelatin and rosella flower extract with osteoblast cells for 24 hours to see whether the rosella extract was toxic to osteoblast cells. Conclusion: This toxicity test shows that rosella flower extract as an ingredient in making scaffolds is not toxic to osteoblast cells.